Data-driven fatigue-oriented MPC applied to wind turbines Individual Pitch Control. (June 2021) - Collet, David; Alamir, Mazen; Di Domenico, Domenico; Sabiron, Guillaume
Abstract: Horizontal Axis Wind Turbine (HAWT) rotor is a system whose components are particularly exposed to fatigue damage, due to non-uniform winds and the rotating nature of the rotor. Individual Pitch Control (IPC) can help alleviating the fatigue loads on the rotor blades by rotating the blades independently from each other on their longitudinal axis. However, reducing the blades fatigue damage is often compensated by an increase in pitch activity, damaging the blade pitch actuators. An IPC regulator must thus optimize a trade-off between the fatigue damage of the blades and blade pitch actuators. This paper presents the derivation and implementation of a fatigue-oriented adaptive Model Predictive Control (MPC) IPC regulator using a data-driven fatigue-oriented cost function. This MPC allows to efficiently optimize the IPC fatigue trade-off and significantly reduce the expectancy of an HAWT rotor economic fatigue cost, compared to a finely tuned non-adaptive MPC. The methodology used for the derivation of the presented MPC allows to efficiently reduce an economic fatigue cost, while limiting the sensitivity to controller tuning. Highlights: Derivation of a data-driven fatigue-oriented cost function. Use of a fixed-point method to solve an fatigue-oriented optimal control problem. Derivation of a fatigue-oriented adaptive MPC based on the fixed-point iterations.